Comparative Analysis of Derivative Parameters of Chemoresistive Sensor Signals for Gas Concentration Estimation - Nina K. Plugotarenko (Chemosensors, 2022)
Signals from resistive gas sensors based on zirconium dioxide and silicon–carbon films have been extensively investigated to estimate gas concentration. In this study, the change in the normalized resistance of the sensor’s response under NO2 exposure is shown and the analysis of the first and second derivatives of the response curves were carried out. A signal-processing scheme, reducing the effect of noise and signal drift, is proposed. The extreme of the second derivative of the sensor response, the initial reaction rate, and the slope of the curve of the approximating line in the coordinates of the Elovich equation are proposed as calibration dependencies. The calibration curves built from the values of the maximum second derivative turned out to be the most stable, with the lowest relative error in estimating gas concentration compared to the traditional fixed-time point method.